The balanced scorecard operating as a risk management tool - Costa Oliveira, Helena (2014)
Balanced Scorecard (BSC) and Enterprise Risk Management (ERM) are useful concepts to the management that pursues methodical business awareness and pays attention to uncertainty and its risks. Very little research has examined the BSC usefulness as an ERM framework. This paper aims to contribute to the debate related to risk management concepts that may be found in the BSC method. Classifying different areas of uncertainty and establishing a hierarchy of risks, the Balanced Scorecard identifies the most important aspects for management concern. It is recognized that BSC’s risk management thinking involves some operational difficulties (mainly linked to information collecting, processing and analysis) that make construction of realistic strategic maps a hard process. However, research literature supports our main assumption that the BSC is a good path of approaching a committed and realistic risk management. The paper is considered an innovative framework to understand and design research on BSC